Moral Values, Sanctity of Life for Nation Building: A Biblical Perspective - Osajie, Justina Nwazuni (NIU Journal of Humanities, 2024)
Nigerians from the onset, have a peculiar culture which is known in their ways of life.  Their values and norms as elements of this their ways of life are embedded in moral education.  However, in Nigerian society today, there is a high rate of negligence of societal moral values while many vices such as: dishonesty, disrespect of elders, insecurity, kidnapping, banditry, raping, corruption, bribery, and many others prevail.  In light of the above, this paper examines the role of moral values and the sanctity of life in nation-building.  Moral education is a means through which individuals are formed and reformed through qualitative training and retraining of human beings who are agents of development in society.  The paper also considers moral education as a means of regenerating these norms and moral values.  Again, the paper discovers among other things that moral values which are seen as behavioural conduct and attitude, should be displayed and encouraged by members of the society to build and revitalized the nation.  Several recommendations were made and emphasis was laid on the need for moral values taught in moral education, with the collaboration of parents and government by imparting good moral values on the Nigerian Citizens. Keywords:  Moral Values, Education, Sanctity of life, Nation Building.